Tag it: Issue 1/October 2012 Are We Visible? - Universiti Malaysia Sarawak, Centre for Information Technology Development & Services (Universiti Malaysia Sarawak (UNIMAS), 2012)
This first edition of Tag-it, seeks to explore the impact of the World Wide Web on Universiti Malaysia Sarawak (UNIMAS). We highlight the impact of social media and look at the criteria used by Malaysia to ensure that all public websites adhere to the highest quality possible.